Relación entre satisfacción laboral y desempeño laboral en colaboradores - Reynalte Gaytán, Lucía Adalia (2024)
Within the organizational context, it has been sought to determine the relationship between job satisfaction and job performance. The objective of this study is to determine the influence of job satisfaction on employee performance. To this end, research were collected from various databases where these variables are related, including Scopus, Web of Science, APA Psycnet and Scielo, through the use of the PRISMA protocol (Page et al., 2021). Thus, ten articles were selected for the study. As a result, it was found that there is a positive correlation between job satisfaction and job performance, given that a worker who shows a high level of job satisfaction tends to perform in a way that achieves organizational objectives. It was also found that the positive relationship between satisfaction and performance is usually mediated by other variables, such as commitment, positive affect, structure or motivation; therefore, the presence of these factors positively influences the relationship between job satisfaction and job performance.